Isovaleric Acidemia: New Aspects of Genetic and Phenotypic Heterogeneity - Vockley, Jerry (2006)
Isovaleric acidemia (IVA) is an autosomal recessive inborn error of leucine metabolism caused by a deficiency of the mitochondrial enzyme isovaleryl-CoA dehydrogenase (IVD) resulting in the accumulation of derivatives of isovaleryl-CoA. It was the first organic acidemia recognized in humans and can cause significant morbidity and mortality. Early diagnosis and treatment with a protein restricted diet and supplementation with carnitine and glycine are effective in promoting normal development in severely affected individuals. Both intra- and inter-familial variability have been recognized. Initially, two phenotypes with either an acute neonatal or a chronic intermittent presentation were described. More recently, a third group of individuals with mild biochemical abnormalities who can be asymptomatic have been identified through newborn screening of blood spots by tandem mass spectrometry. IVD is a flavoenzyme that catalyzes the conversion of isovaleryl-CoA to 3-methylcrotonyl-CoA and transfers electrons to the electron transfer flavoprotein. Human IVD has been purified from tissue and recombinant sources and its biochemical and physical properties have been extensively studied. Molecular analysis of the IVD gene from patients with IVA has allowed characterization of different types of mutations in this gene. One missense mutation, 932C>T (A282V), is particularly common in patients identified through newborn screening with mild metabolite elevations and who have remained asymptomatic to date. This mutation leads to a partially active enzyme with altered catalytic properties; however, its effects on clinical outcome and the necessity of therapy are still unknown. A better understanding of the heterogeneity of this disease and the relevance of genotype/phenotype correlations to clinical management of patients are among the challenges remaining in the study of this disorder in the coming years.